2010
DOI: 10.3390/molecules15063775
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolo[3,2-a]benzimidazoles: Synthetic Strategies, Chemical Transformations and Biological Activities

Abstract: The present review covers the recent synthetic strategies and chemical transformations of thiazolo[3,2-a]benzimidazoles and it also presents the highlights of the biological activities of these compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 101 publications
(126 reference statements)
0
37
0
1
Order By: Relevance
“…Thus, cyclocondensation of 2‐aminonitriles with formamide afforded the corresponding aminopyrimidine derivatives . In the present investigation, compound 2 was obtained through reaction of compound 1 with an excess formamide without solvent.…”
Section: Resultsmentioning
confidence: 92%
“…Thus, cyclocondensation of 2‐aminonitriles with formamide afforded the corresponding aminopyrimidine derivatives . In the present investigation, compound 2 was obtained through reaction of compound 1 with an excess formamide without solvent.…”
Section: Resultsmentioning
confidence: 92%
“…The reaction of 2-mercaptoimidazoles with N-(sulfonyl)phenyldichloroacetaldimines leads to the formation of N-(2-phenylimidazo [2,1-b] [1,3]thiazol-3-yl)arenesulfonamides or N-(2-phenyl [1,3]thiazolo [3,2-a]benzimidazol-3-yl)arenesulfonamides. The advantages of the method for the preparation of the imidazothiazole and thiazolobenzimidazole derivatives are available starting reagents, catalyst-free one-step procedure, and high selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…1 The prospects for application of biologically active imidazothiazoles stem from their ability of inhibiting or activating the various enzymes and receptors. [2][3][4][5] Importantly, these compounds show antitumor, [6][7][8][9][10][11] antimicrobial, 12,13 antidiabetic, 14 diuretic, 15 antihelmintic, 16 and fungicidal 17 properties.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, previous studies have shown that the use of thiazole-based compounds as starting materials in organic synthesis led to the formation of several thiazole-derivatives with a wide spectrum of biological activities [21,22] such as antifungal [23,24], antimicrobial [25e27], antimalarial [28] and anticancer [29e35].…”
Section: Introductionmentioning
confidence: 99%